Analysis of the Quality of the Registration Services of Haji Travelers in the Office of the Ministry of Religion, Bengkulu City - Aldi Syafitra Anwari; Sulisti Apriani; Abdul Rahman (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to analyze the quality of service for the registration of pilgrims at the Office of the Ministry of Religion of the City of Bengkulu, Permenpan RB Number 14 of 2017. The sampling method was used by simple random sampling with a sample size of 100 pilgrims who registered for the pilgrimage. The method of analysis in this research is qualitative and quantitative analysis based on Permenpan RB Number 14 of 2017. The results of the study show that the quality of the Hajj pilgrims 'registration service in the PHU Section of the Office of the Ministry of Religion of Bengkulu City with the criteria of